Implementation of Problem Based Learning using Interactive Media Canva and Quizziz to Improve Problem Solving Abilities of Vocational High School Students - Pujiyastuti, Heti; Sabandar, Jozua; Afrilianto, M. (IKIP Siliwangi, 2025)
Problem-solving ability is an essential skill that must be possessed by students, especially in Vocational High Schools (SMK), in order to apply the concepts learned in real situations. However, many students have difficulty in identifying and solving mathematical problems because the learning method is still centered on the teacher and the minimal use of interactive learning media. This study aims to analyze the mathematical problem-solving ability of vocational high school students whose mathematics learning uses the Problem Based Learning model assisted by interactive media canva and quizizz compared to those who use regular learning. This study uses a quasi-experimental method with a Nonequivalent Control Group Design. The research sample consisted of 64 grade XI students of SMKN 1 Cariu, which were divided into an experimental class (32 students) who received learning using PBL assisted by interactive media Canva and Quizizz, and a control class (32 students) who used regular learning methods. Data collection was carried out through problem-solving ability tests (pretest and posttest), questionnaires and observations. Data analysis using inferential statistics, namely the average difference test with N-Gain as a measure of learning outcomes, and thematic analysis for qualitative data. The results of the study showed that the mathematical problem-solving ability of vocational high school students whose mathematics learning used the Problem Based Learning model assisted by interactive media canva and quizizz was better than those who used regular learning.